akuntansi ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT UNTUK MENILAI KINERJA KEUANGAN PADA PT GUNUNG RAJA PAKSI TBK - Fitri Handayani (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
PT Gunung Raja Paksi's financial condition for a period of 5 years, namely from 2017-2021, experienced unfavorable conditions because it experienced losses in 2018-2020. This study aims to determine the financial performance of PT Gunung Raja Paksi, which is measured using the cash flow ratio. This study uses a qualitative descriptive analysis method, then analyzed using a cash flow ratio which consists of the ratio of operating cash flows to current liabilities (AKO), cash flow adequacy ratio (KAK), cash flow ratio to capital expenditure (PM), fund flow coverage ratio ( CAD), and Total Debt Ratio (TH). Free Net Cash Flow Ratio (AKBB). The results of this study indicate that the company's total cash flow during the 2017-2021 period at PT Gunung Raja Paksi is not good enough. This can be seen from the value of cash flow ratios that are still below standard 1 as in the AKO ratio of 0.031 times, -0.203 times, 0.287 times, 1.258 times, 0.340 times, ratios of AKO -0.423 times, -0.203 times, -6.205 times , -5.934 times, 3.792 times, PM ratio0.218 times, -0.834 times, 4.016 times, 2.637 times, 1.048 times, CAD ratio 0.085 times, -0.846 times, 1.821 times, 3.738 times, 2.159, TH ratio 0.013 times, - 0.106 times, 0.221 times, 0.689 times, 0.205 times, and the AKBB ratio -0.337 times, -0.443 times, 0.129 times, 0.921 times, 0.183 times. Keywords: Financial Performance, Cash Flow Statement, Cash Flow Ratio.